PROSPECTS OF USE OF INNOVATIVE TECHNOLOGIES IN EDUCATION - Shirinov Feruzjon Shuxratovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the prospects for the use of innovative technologies in education and modern educational technologies.